QRIS Management Assistance for MSME Players through Digital Platforms - Hakim, Abdurrahman (Lembaga Dongan Dosen, 2025)
Digitalization plays a crucial role in business payment systems, offering significant benefits such as payment efficiency and automated cash flow recording, which reduces the risk of input errors. Additionally, digitalization facilitates access to global markets, enabling businesses to operate internationally more effectively while reducing additional costs like administration and transportation typically associated with traditional payment methods. Digital payment platforms are equipped with stringent security protocols to protect financial data and transactions, minimizing the risk of fraud. One popular digital payment system is QRIS (Quick Response Indonesian Standard), which unifies various QR codes from different payment service providers through a QR code developed in collaboration with Bank Indonesia. However, the implementation of QRIS faces administrative and technical challenges, such as aligning standards among service providers and ensuring adequate internet access. Nevertheless, QRIS is expected to simplify access to digital payment facilities for business operators, enhancing business efficiency and effectiveness. The community service method employed involves training and technical assistance for MSMEs through a specially designed digital platform, resulting in a significant increase in understanding and adoption of QRIS, expanding market reach, and improving MSME competitiveness